Circulating androgens in women: Exercise-induced changes - Enea, C.; Boisseau, N.; Fargeas-Gluck, M. A.; Diaz, V.; Dugue, B. (Sports Medicine, 2010)
Physical exercise is known to strongly stimulate the endocrine system in both sexes. Among these hormones, androgens (e.g. testosterone, androstenedione, dehydroepiandrosterone) play key roles in the reproductive system, muscle growth and the prevention of bone loss. In female athletes, excessive physical exercise may lead to disorders, including delay in the onset of puberty, amenorrhoea and premature osteoporosis. The free and total fractions of circulating androgens vary in response to acute and chronic exercise/training (depending on the type), but the physiological role of these changes is not completely understood. Although it is commonly accepted that only the free fraction of steroids has a biological action, this hypothesis has recently been challenged. Indeed, a change in the total fraction of androgen concentration may have a significant impact on cells (inducing genomic or non-genomic signalling). The purpose of this review, therefore, is to visit the exercise-induced changes in androgen concentrations and emphasize their potential effects on female physiology. Despite some discrepancies in the published studies (generally due to differences in the types and intensities of the exercises studied, in the hormonal status of the group of women investigated and in the methods for androgen determination), exercise is globally able to induce an increase in circulating androgens. This can be observed after both resistance and endurance acute exercises. For chronic exercise/training, the picture is definitely less clear and there are even circumstances where exercise leads to a decrease of circulating androgens. We suggest that those changes have significant impact on female physiology and physical performance.